EFEKTIVITAS PENGGUNAAN MODEL PEMBELAJARAN INKUIRI DALAM MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA PADA PEMBELAJARAN IPS DI SEKOLAH DASAR THE USE OF INQUIRY MODELS TO IMPROVE STUDENTS' CRITICAL THINKING ABILITIES IN SOCIAL STUDIES LEARNING IN ELEMENT - Izzah, Aisyah Nurul; Erwandi, Asilah Muthi’ah; Sanjaya, Nisrina Ayu Anareta; Marini, Arita; Yunus, Mahmud (Sindoro: Cendikia Pendidikan, 2024)
Critical thinking is very much needed by students to prepare themselves to face the progress of science and technology in the 21st century. To anticipate this, various reforms and improvements need to be made in the world of education. One of them is the renewal and improvement of the learning model. This research seeks to examine existing literature on the effectiveness of the inquiry-based learning model in enhancing critical thinking abilities among elementary school students in social studies. the study employs a qualitative approach, utilizing descriptive analysis techniques and a literature review. Findings from previous literature reveal that implementing the inquiry learning model can foster improvements in students' critical thinking skills, meaning that the use of the inquiry model is quite effective in various subjects, including social studies subjects. Kemampuan berpikir kritis menjadi hal esensial bagi siswa dalam mempersiapkan diri menghadapi perkembangan IPTEK di abad ke-21. Untuk menghadapi tantangan ini, diperlukan berbagai inovasi dan perbaikan dalam sektor pendidikan, salah satunya adalah peningkatan metode pembelajaran. Dasar dari penelitian untuk memperoleh tinjauan literatur terkait efisiensi metode pembelajaran tipe inkuiri demi peningkatan kemampuan berpikir kritis siswa pada bidang ilmu IPS di tingkat sekolah dasar. Pendekatan penelitian yang dimanfaatkan bersifat kualitatif dengan metode analisis deskriptif maupun studi pustaka. Berdasarkan hasil dari kajian literatur, penerapan model pembelajaran inkuiri terbukti mampu mengembangkan keahlian pola pikir kritis siswa, menunjukkan bahwa model ini efektif diterapkan di berbagai mata pelajaran, termasuk IPS